Microwave- and ultrasound-assisted extraction of phenolic and flavonoid compounds from konar (Ziziphus spina-christi) fruits - Keshavarz, B. (2023)
Konar (Ziziphus spina-christi) fruit is known to have antioxidant and anti-inflammatory properties. In the present work, we investigated the yields for microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), and magnetic stirrer extraction (MSE) methods using different extraction parameters including type of solvent, solvent to sample ratio (SSR), microwave irradiation power, extraction temperatures for MSE, microwave irradiation time, sonication time for UAE, and extraction time for MSE on the total phenolic (TP) and total flavonoid (TF) contents of the underutilised nutritious konar fruit. The highest TP content was obtained by MAE using water as solvent [10.3 ± 0.1 mg tannic acid equivalent (TAE) per gram (g) of sample]. However, the highest TF contents were obtained using ethanol in MAE [1.9 ± 0.0 mg quercetin equivalent (QE) per g of the sample], and methanol in UAE and MSE [1.7 ± 0.0 mg QE per g of sample]. An SSR of 15 resulted in the highest TP content while no significant differences were observed in the TF contents. MAE was considered the best extraction method for the extraction of TP and TF from konar fruits as demonstrated in the present work.